Pediatric refractory and super-refractory status epilepticus. (May 2019) - Vasquez, Alejandra; Farias-Moeller, Raquel; Tatum, William
Highlights: Pediatric RSE and SRSE are neurological emergencies with high morbidity and mortality. NORSE and FIRES are relatively rare epilepsy syndromes, but common in SRSE population. Treatment approaches are variable and with limited evidence after anesthetic agents. Prolonged seizures and hospital stay lead to neurologic and systemic complications. Abstract: Purpose: To summarize the available evidence related to pediatric refractory status epilepticus (RSE) and super-refractory status epilepticus (SRSE), with emphasis on epidemiology, etiologies, therapeutic approaches, and clinical outcomes. Methods: Narrative review of the medical literature using MEDLINE database. Results: RSE is defined as status epilepticus (SE) that fails to respond to adequately used first- and second-line antiepileptic drugs. SRSE occurs when SE persist for 24 h or more after administration of anesthesia, or recurs after its withdrawal. RSE and SRSE represent complex neurological emergencies associated with long-term neurological dysfunction and high mortality. Challenges in management arise as the underlying etiology is not always promptly recognized and therapeutic options become limited with prolonged seizures. Treatment decisions mainly rely on case series or experts' opinions. The comparative effectiveness of different treatment strategies has not been evaluated in large prospective series or randomized clinical trials. Continuous infusion of anesthetic agents is the most common treatment for RSE and SRSE, although many questions on optimal dosing and rate of administration remain unanswered. The use of non-pharmacological therapies is documented in case series or reports with low level of evidence. In addition to neurological complications resulting from prolonged seizures, children with RSE/SRSE often develop systemic complications associated with polypharmacy and prolonged hospital stay. Conclusion: RSE and SRSE are neurological emergencies with limited therapeutic options. Multi-national collaborative efforts are desirable to evaluate the safety and efficacy of current RSE/SRSE therapies, and potentially impact patients' outcomes.